Peranan Strategi Guru dalam Mengembangkan Karakter Islami Anak di Sekolah - Anwar, Syaiful (Universitas Islam Negeri Raden Intan Lampung, 2016)
Moral degradation that is now going on in Indonesian, assumed was sourced from ethical and moral crisis in religion. Akhlak and moral crisis is an indication of poor mentality of the nation and the decline of the national dignity. It can be one of sign to the destruction of the nation. Responding to these conditions, lately, character education has become one of the hot issues in education. Program of